Report on practice-in-industry training in fish culture - Belencion, Sonia Bermijo (College of Fisheries, University of the Philippines, 1966)
The cultivation of bañgos or milkfish is very lucrative and is becoming a highly developed industry in the Philippines. It is one of the specialized industries, which involve experience and technique in preparation and management. The marked increase of fishpond under cultivation since the introduction of bañgos culture in the Philippines, may be attributed to the great enthusiasm of the people venturing in this industry engendered by the demonstrations and technical assistance of the Fisheries Commission through it different demonstration fish farms. In spite of our earnest development of our fishpond industry, we cannot neglect the fact that we are in a shortage of fish for our home consumption. We have very rich natural resources, but few are diligently exploiting them. With this condition of our natural resources, improvements and developments are necessary so as to supply the thirty one million fast exploding Filipino fish eaters, requiring 800,000 tons of fish annually. Because our catch is insufficient, we import from the neighboring countries about 65,000 tons of fish annually valued at about 30 million pesos. Such amount could be saved or spent on other items if only we could increase our productive capacity in fish industry. Anyway we are still fortunate enough to have plenty of room for expansion. There are more or less 600,000 hectares of saltwater mangroves and freshwater swamps, the greater portion of which is suitable for fishpond purposes. If all of those will be adequately explored and developed, we will be benefited of the rich potential for home consumption, for commerce, for industry and for export to foreign lands.